2014
DOI: 10.1111/ijlh.12203
|View full text |Cite
|
Sign up to set email alerts
|

CD14+HLADR low/ monocytes as indicator of disease aggressiveness in B‐cell non‐Hodgkin lymphoma

Abstract: Increased CD14(+) monocytes with loss of HLA expression were seen in patients with higher stage disease, more aggressive pathology, and in relapse or refractoriness to treatment. Identifying therapeutic strategies to overcome the suppressive properties of these monocytes could be of value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…5,[8][9][10]12,14 We hypothesized that CD14 C HLA-DR low/neg monocytes adopt this phenotype through tumor-mediated factors. We found that lymphoma tumors are frequently heavily infiltrated with CD14 C cells (Fig.…”
Section: Lymphoma Cells Convert Monocytes To An Immune Suppressive Phmentioning
confidence: 99%
See 1 more Smart Citation
“…5,[8][9][10]12,14 We hypothesized that CD14 C HLA-DR low/neg monocytes adopt this phenotype through tumor-mediated factors. We found that lymphoma tumors are frequently heavily infiltrated with CD14 C cells (Fig.…”
Section: Lymphoma Cells Convert Monocytes To An Immune Suppressive Phmentioning
confidence: 99%
“…5,13 In addition, decreased presence of these cells is associated with improved clinical response to treatments. 12,14 In this study, we examined lymphoma and monocyte crosstalk that promote lymphoma survival. Using mouse models to mimic our previous findings is difficult.…”
Section: Introductionmentioning
confidence: 99%
“…CD14 is a myeloid differentiation marker expressed primarily on monocytes/macrophages. Recently, it was shown that NHL patients with a more aggressive disease phenotype exhibited high expression of CD14 and low expression of HLA‐DR (CD14 + HLA‐DR − /low) that suppresses normal immune function and the proliferation of normal T‐cells . Moreover, lymphoma cells treated with CD14 + HLA‐DR − /low monocytes exhibited chemotherapeutic resistance to doxorubicin.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple myeloma PMN-MDSCs are induced by multiple myeloma-related mesenchymal stem cells to have high expression of ARG1 and exert immunosuppressive function in tumor [103] Multiple myeloma PMN-MDSCs limit the anti-tumor response of T cells by increase the expression of ARG1 and other suppressive molecules, which is correlated with the expression of IL-18 [104] Head and neck cancer and urological cancers Overexpression of fatty acid transport protein 2 (FATP2) in PMN-MDSCs is conductive to tumor growth by the synthesis of PGE2 [29] Lymphomas are malignant tumors derived from the lymphatic hematopoietic system and are divided into Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL) [106]. Several studies have uncovered that in NHL, including B cell NHL, diffuse large B cell lymphoma and NK/T cell NHL, increased expression of ARG1, IDO and iNOS in MDSCs is relevant to the enhancement of tumor growth and suppression of T cells [107][108][109][110]. However, little is known about whether the metabolic regulation of MDSCs participates in HL [111].…”
Section: Arg1mentioning
confidence: 99%